Comparison of Cognitive Behavioral Therapy and Mindfulness on Anxiety, and Positive and Negative Affect in Female Students - Shabannezhad, Ariana (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The aim of the present research was to compare cognitive behavioral therapy and mindfulness on anxiety, and positive and negative affect in female students of Sari city.Methods and Materials: The design of the current study was applied in purpose and quasi-experimental in execution, with a pre-test and post-test design, two experimental groups, one control group, and a follow-up period of two months. The research population consisted of all female students who visited a private counseling center in Sari city in 2023, from whom 30 individuals were selected through convenience sampling and randomly assigned to two experimental groups and one control group. Furthermore, to collect information, the Positive and Negative Affect Scale by Tellegen and Watson (1985) and the Zung Self-Rating Anxiety Scale (1971) were used. For statistical analysis of the data, SPSS-26 software and three-way repeated measures analysis of variance and Bonferroni post hoc test were utilized.Findings: The findings indicate that there was a significant difference between the pre-test and post-test scores for both approaches for negative affect, positive affect, and anxiety (p < .01), demonstrating the significant effectiveness of these two therapeutic methods. Moreover, no significant difference was observed between the post-test scores and the follow-up stage (p > .05). Analysis using the Bonferroni test reveals that the difference in effectiveness between the two teachings on problem-solving components is not significant (p > .05).Conclusion: Based on the findings, it can be concluded that both cognitive behavioral therapy and mindfulness therapy can be used to reduce depression and negative emotions and to increase positive emotions in female students, with no significant difference in the effectiveness of these therapeutic methods.